Prognostic value of EEG in West syndrome - Nikolić, Dimitrije M.; Milovanović, Ivan D.; Medjo, Biljana P.; Atanasković, Marina; Ivanovski, Petar I.; Nikolić, Ana V. (Vojnosanitetski pregled, 2020)
Background/Aim. West syndrome (WS) is an epileptic encephalopathy which is characterized by the trias: infantile spasms, psychomotor delay and specific electroencephalography (EEG) pattern. The aim of this study was to determine the prognostic value of EEG in the therapy of West syndrome. Methods. This study group comprised 68 patients (40 boys and 28 girls) with the diagnosis of WS. Criteria for inclusion of patients in this study were the disease onset in the first or the second year of life, specific seizure type and a characteristic EEG pattern. All patients were divided into 2 groups: symptomatic (37 patients) and cryptogenic (31 patients) WS. The outcome was assessed through the response to the therapy (seizure control and EEG findings). Follow-up was at 3, 6, 12 and 24 months after the diagnosis was established. Results. Three months after starting the treatment 80.6% of patients with improved EEG were seizure free (p < 0.01); 85.7% of patients with EEG improvement at 3 months check-up were seizure free after 6 months (p < 0.01); 82.8% of patients with better EEG findings after 3 months had no seizures after 12 months (p < 0.05). Also, the majority of patients with improvement in EEG at 6 month follow-up (95.8%) had no seizures at one year follow-up (p < 0.01). The presence of seizures during this period did not depend on EEG after 6 months of treatment (p > 0.05). Most of the patients with improved (89.7%) and unchanged (70.6%) EEG after 12 months had no seizures after two years, whereas the patients with worsened EEG were with seizures. Conclusion. Seizure control after 6, 12 and 24 months depended on EEG finding at 3 months follow up. Seizure control after 12 months correlated with EEG after 6 months. The correlation between EEG after 12 months and seizure control after 24 months was not clear. EEG at 6 months follow-up did not affect seizure control after 2 years.
Keywords: electroencephalography; prognosis; treatment outcome; spasm; infant, newborn; epilepsy.